PENGARUH INDUSTRIAL TYPE, LIKUIDITAS DAN COMPANY SIZE TERHADAP PENGUNGKAPAN RISK MANAGEMENT PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ninta, Deva; Pasaribu, Dompak; Sagala, Lamria (MTU PRESS, 2023)
This research aims to examine the influence of industrial type, liquidity and company size on risk management disclosure. Industrial type is proxied using the average number of employees, liquidity with the current ratio and company size with total assets. The research uses multiple linear regression methods with a sample size of 24. The research population is LQ 45 companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling technique is the purposive sampling method. The research results show that the industrial type and liquidity variables have a positive and insignificant effect on risk management disclosures, company size has a positive and significant effect on risk management disclosures.